NELFT Adult Autism Service Quality Improvement Project: Managing Demand, Capacity and Flow of Referrals for Adult Autism Assessments - Fahima Khanom; Saras Saminathan (BJPsych Open)
Aims: The team joined the Royal College of Psychiatrists Quality Improvement (QI) Demand, Capacity and Flow (DCF) Collaborative. The aim was to increase the discharge rate to 19 per month following specialist assessment by June 2024.